(untitled) (Conference on English Language Teaching, 2023)
This study aims to determine the strategies used by teachers in teaching English, especially reading comprehension with E-learning mode during the pandemic. This research is located in MTsN 02 Palembang. Qualitative methods with case studies were used in this study. In conducting this research, data were collected from three eight grade English teachers. Semi-structured interviews were conducted for know the strategies used in teaching reading based on the experience of each teacher. Result of this study shows that the teachers used several strategies in the learning process through E-learning. That is, the teacher used various strategies in each meeting. As a result, the use of several strategies implemented by teachers can assisting teachers in teaching English through E-learning.